HUBUNGAN ANTARA JENIS INSISI KATARAK DENGAN KEJADIAN SINDROMA MATA KERING PADA PASIEN PASCA OPERASI KATARAK DI RUMAH SAKIT MATA BALI MANDARA - I Nyoman Widiadnyana; I Kadek Nuryanto; I Gusti Ngurah Made Kusuma Negara (Jurnal Riset Kesehatan Nasional, 2018)
Background: Cataract surgery is a surgery for cataract patients. This surgery has some complications, such as the occurrence of dry eyes syndrome. There are two techniques of cataract surgery; they are Phacoemulsification and SISC with different type of incision. The purpose of this study was to determine the relationship between the types of cataract incision with the incidence of dry eyes syndrome. Methods: This study used descriptive correlation design with cross-sectional approach. The sampling technique used was non-probability sampling with consecutive sampling technique. The total sample used in this study were 78 respondents, in which 51 respondents had undergone Phacoemulsification incision and 27 respondents had undergone SICS incision. The data collection tool used was the OSDI questionnaires. Results: 10 respondents who had the SISC and 5 respondents who had the Phacoemulsification experienced dry eyes syndrome. The result of Chi Square test showed that p-value was 0.009; which means there was a significant relationship between the types of cataract incision with the incidence of dry eyes syndrome. Conclusion: The types of cataract incision had a significant relationship to the occurrence of dry eyes syndrome. Therefore, nurses are expected to be able to provide care and give CIE (communication, information, and education) to reduce the complications. Keywords: cataract, dry eyes syndrome, type of incision